Chronic inflammation predicts long‐term mortality in patients with Raynaud's phenomenon. (14th November 2017) - Mueller, M.; Gschwandtner, M. E.; Gamper, J.; Giurgea, G.‐A.; Kiener, H. P.; Perkmann, T.; Koppensteiner, R.; Schlager, O.
Abstract: Background: Subclinical chronic inflammation could be the driving force behind the recently revealed association between abnormal nailfold capillaries as well as autoantibodies and long‐term mortality in patients with incipient Raynaud's phenomenon. Whether laboratory markers that reflect a chronic inflammatory process are directly related to mortality in Raynaud's phenomenon is not known. Methods: In total, 2958 patients with incipient Raynaud's phenomenon without previously known connective tissue disease (CTD) were enrolled. At their initial presentation, laboratory tests for C‐reactive protein (CRP), leucocytes, fibrinogen and the haemoglobin concentration were obtained. In addition, nailfold capillaries and antinuclear antibodies (ANA) were assessed. Patients' mortality was recorded through a median follow‐up period of 9.3 years. Results: Baseline CRP, fibrinogen and haemoglobin concentration were associated with long‐term mortality in an individual analysis of patients with incipient Raynaud′s phenomenon. In a multivariable model including patients' age, nailfold capillaries and ANA, a low haemoglobin concentration remained independently related to future mortality. Amongst potential predictors for mortality in patients with Raynaud's phenomenon, a low haemoglobin concentration was most strongly related to patients' mortality risk. Conclusion: In Raynaud's phenomenon, laboratory markers that can be attributed to a chronic inflammatory state independently yield prognostic information in addition to the presence of abnormal nailfold capillaries and ANA. Amongst all prognostic markers, the haemoglobin concentration is most strongly related to patients' mortality in Raynaud's phenomenon.